Intervertebral disk nutrition: a review of factors influencing concentrations of nutrients and metabolites. - Grunhagen, T; Shirazi-Adl, A; Fairbank, J; Urban, J (2011)
The biomechanical behavior of the intervertebral disk ultimately depends on the viability and activity of a small population of resident cells that make and maintain the disk's extracellular matrix. Nutrients that support these cells are supplied by the blood vessels at the disks' margins and diffuse through the matrix of the avascular disk to the cells. This article reviews pathways of nutrient supply to these cells; examines factors that may interrupt these pathways, and discusses consequences for disk cell survival, disk degeneration, and disk repair.